A singular boundary value problem for neutral equations - Vasil G. Angelov (International Journal of Mathematics and Mathematical Sciences)
Using some previous results of the author and Kirk-Schöneberg, theorems for the existence and uniqueness of an absolutely continuous solution of a singular boundary value problem for neutral equations have been proved.